What can influence the outcome of open wedge high tibial osteotomy? - V. E. Bialik; S. A. Makarov; M. A. Makarov; E. I. Bialik; V. A. Nesterenko; M. R. Nurmukhametov; D. V. Kapitonov; A. A. Chernikova (Научно-практическая ревматология)
Objective – to assess the effect of patient-specific parameters (age, body mass index (BMI), stage of the knee osteoarthritis (KOA), the osteotomy gap size, concomitant medial opening angle high tibial osteotomy (MOWHTO) arthroscopic plastic (AP) and open chondroplasty (OCHP) on the development of complications and the outcome of the operation.Materials and methods. The study included 76 patients who underwent MOWHTO. To study the influence of each of the parameters, comparison groups were created: 1) by age: patients younger and older than 60 years (45 versus 31); 2) by BMI: patients with BMI<30 kg/m2 versus patients with a BMI from 30 to 40 kg/m2 (35 versus 41); 3) by the osteotomy gap size: ≤10 mm and >10 mm (29 versus 47); 4) by stages of KOA: patients with stage I and II versus patients with stage III (43 versus 33); 5) patients with MOWHTO + AP of the knee or OCHP versus patients who underwent only MOWHTO (34 versus 42). To assess the result, we studied the change in pain intensity according to the visual analogue scale (VAS), as well as the state of the knee joint according to the Knee Society Score (KSS) scale before surgery and 1 year after MOWHTO.Results. The development of complications had a weak direct relationship with stage III of the KOA (r=–0.24) and moderate strength a direct relationship with the osteotomy gap size >10 mm (r=–0.42). Age, BMI, the presence of concomitant AP of the knee or OCHP did not affect the development of complications. However, the number of complications was statistically significantly higher among patients with stage III and osteotomy gap size >10 mm relative to patients with stage II of the KOA (p=0.03) and patients with deformity correction ≤10 mm (p=0.0002). Age over 60 years and BMI<30 kg/m2 had a direct weak relationship (r=0.27 and r=0.23) with the achievement of a satisfactory result. An excellent result had a direct weak relationship with a BMI<30 kg/m2 and stages I–II of the KOA (r=0.34 and r=0.31), as well as a direct moderate strength relationship with an osteotomy gap size ≤10 mm (r=0.46). At the age of patients over 60 years, a satisfactory result was significantly more frequent compared with patients of young and middle age (p=0.016). 71.1% of excellent results were obtained in patients with a BMI<30 kg/m2 (p=0.002), and there were significantly more good and satisfactory results in the group of patients with a BMI>30 kg/m2 (p=0.08 and p=0.04). At stage III, an excellent result was obtained 3 times less frequently than in patients with stages I and II of the KOA (p=0.004). In patients with gap size ≤10 mm, excellent results were 1.5 times greater than in patients with a gap size >10 mm (p=0.00006). There were no differences in the results in patients who underwent MOWHTO in isolation and in patients in whom MOWHTO was supplemented with AP of the knee or OCHP.Conclusions. The development of complications is associated with stage III of the KOA and the need for correction (the osteotomy gap size) >10 mm. The best result of MOWHTO can be obtained in patients under the age of 60 years, with a BMI <30 kg/m2 at stages I–II of the KOA and deformity correction within 10 mm. Concomitant AP of the knee or OCHP don’t affect the development of complications and the outcome of the operation.